The utility of the implantable loop recorder in patients with a diagnosis or family history of long QT syndrome. (14th October 2021) - Balfe, C; Durand, R; Jain, D; McKearney, E; Sheahan, R; Crinion, D; Ward, D
Abstract: Background: There is limited published data on the use of implantable loop recorders (ILRs) in patients with long QT syndrome (LQTS). Purpose: We sought to evaluate the utility of the ILR in patients who had a diagnosis of LQTS or who had a family history of LQTS. Methods: We carried out a retrospective analysis of patients attending an Inherited Cardiac Conditions Clinic who had an active ILR and who had a diagnosis or family history of LQTS. Patient demographics, indications for ILR implantation and clinical outcomes were compiled. Results: Nine patients with a diagnosis of LQTS and an active ILR were identified with an average age of 37 years. Genetic results were available for seven patients. Four patients had a confirmed pathogenic mutation (one KCNQ1 and three KCNH2), one patient had a variant of uncertain significance in SCN5A and two patients had negative genetic testing. Indications for implantation were syncope (n=4), recurrent altered consciousness episodes (n=1), assessment of occult arrhythmia or beta blocker complications (n=2), palpitations and dizziness (n=1) and nocturnal dyspnoea and palpitations (n=1). Mean follow-up was 706 days and average age at ILR implant was 35 years. The ILR for three patients was a second device, implanted after end of battery life of the initial ILR. ILR recordings led to a change in management in three patients: finding of paroxysmal atrial fibrillation (n=1), finding of nocturnal QTc of 511ms with a change in medications (n=1) and a pause leading to cessation of beta blocker (n=1). Eleven patients with a family history of LQTS and active ILR were identified. Nine patients were female, and the average age was 44.4 years. Genetic test results were available for five patients. Three patients had a pathogenic mutation in SCN5A, and two patients had negative genetic testing for common LQTS genes. Indications for implantation included syncope (n=5), lightheaded episodes (n=3) and risk assessment in gene carriers (n=3). The mean duration of ILR follow-up was 680 days and average age at ILR implant was 42.5 years. Five patients had no arrhythmia detected during ILR recording, two patients had supraventricular tachycardia identified, in two patients ILR data outruled a sinister cause for a symptomatic episode, one patient had documentation of SVT and brief NSVT which led to referral for electrophysiology study and one patient had no recurrence of symptoms and a second ILR was implanted. Conclusion: ILRs were inserted in selected patients with a diagnosis of LQTS or in patients with a family history of LQTS or who were gene carriers. Rationale for ILR implantation included risk stratification, monitoring for occult arrhythmia and rhythm-symptom correlation in symptomatic patients. The ILR impacted management in almost 50% of patients and is considered an important tool in selected patients attending Inherited Cardiac Condition Clinics. Funding Acknowledgement: Type of funding sources: None.